FORMULATION AND CHARACTERIZATION OF SUNSCREEN MICROEMULSION OF PINEAPPLE EXTRACT (Ananas comosus (L.)) WITH SYNERGISTIC EFFICACY ON SUN PROTECTION FACTOR (SPF) - Mutiah, Roihatul; Sukma, Yolanda Cahyaning; Megawati, Dewi Sinta; Annisa, Rahmi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The root of Calotropis gigantea (thistle) is an Indonesian herb to treat cancer based on empirical and scientific evidences. The study aims to find out the infuence of ethanol extract of Calotropis gigantea root in inhibiting cancer cell growth of Mus musculus fibrosarcoma in vivo and to find out metabolite compound in the Calotropis gigantea root extract. The effect of cancer cell growth inhibition was tested on Mus musculus inducted with 7.12-dimetilbenz (Î±) antrasena (DMBA) and dose treatment of 50, 100 and 150 mg/Kg body weight. The metabolomic analysis on the root employs UPLC-QToF-MS/MS as a positive ESI ion source, the movement phase of water/acid mixture is 99.9/0.1 [v/v] and acetonitrile/formic acid was 99.9/0.1 [v/v] with gradient elution system and stationary phase of C18. The chromatogram was analyzed using Masslynx 4.1. The component identification was based on the m/z ratio measured in Masslynx and m/z counted in chemdraw. The result of the study showed that the Calotropis gigantea root extract with the dose of 50, 100 dan 150 mg/Kg body weight were able to increase the weight of fibrosarcoma mice and have a significant influence on caspase-3 expression with cell apoptosis index 24.3 %; 13.3 % and 12.3 % respectively. The result of metabolomic analysis showed 14 compounds found in the root extract. There are two major compounds: 4-Chlorobenzenethiol with the area 32.51% and N-[1-(Adamantan-1-yl) ethyl]-2-(1-piperidinyl)-4-quinazolinamine with the area 37.20%. They are indicated responsible for the anticancer activity of Calotropis gigantea root extract.Â Keywords: Calotropis gigantea, caspase-3, fibrosarcoma, metabolomic, UPLC-QToF-MS/MS